PENANGKAPAN RADIKAL 2,2-difenil-1-pikril hidrazil (DPPH) BUAH PEPAYA (Carica papaya L. (jingga)) TUA DAN MUDA - Emir Ramadhan; Sudarsono Sudarsono (Faculty of Pharmacy, Universitas Gadjah Mada, 2013)
Some compounds were potentially as a radical catcher, it was also found in the papaya fruit (Carica papaya L. (orentang)). This study aimed to determine 2,2-diphenyl-1-pycrylhydrazyl (DPPH) radical capture of ripe and raw papaya fruits with vitamin C synthetic as a benchmark. Mashed papaya pulp was dried by the freeze-drying method. The dryed mass was dissolved in ethanol and reacted with DPPH. Vitamin C was also treated by the same method, then made a standard and curve of percent DPPH radical arrest by vitamin C. Percent DPPH radical capture by the ripe and raw papaya fruit powder extracts was plotted on a standard curve. Ripe papaya fruit had the ability to capture the highest DPPH radical (1.340,931 mg of fresh ripe papaya proportional to 1 mg of vitamin C). The raw papaya had the capability of 3.557,814 mg of fresh raw papaya proportional to 1 mg of vitamin C.